STRATEGI PEMBELAJARAN PENDIDIKAN KRISTEN BAGI JEMAAT DEWASA DI GEREJA BEM TAMAN TUNKU MIRI, MALAYSIA - Paulus Labai (Sekolah Tinggi Teologi Excelsius, 2018)
Abstract: Christian education learning serves as a guide to help Christian educators in training adults in the church so that the congregation will understand more about the image or concept of identity, role and responsibility as adults more clearly and steadily in everyday life and in their relationship with society. around. The problems that arise are: What is the definition of adult andragogy? What is the significance of Christian education for adults? What is the Christian education learning strategy for adult congregations in the BEM Taman Tunku Miri church, Malaysia? The answers to the problems are: (1) Christian education for adult congregations is an effort to educate or educate church members in all existing age groups, including the adult age group. (2) significant Christian education for adults is one form of the church's efforts in educating or educating its citizens by planning a learning program designed in such a way as to achieve the goals of Christian education for adults. (3) The Christian education learning strategy for adult congregations at the BEM Taman Tunku Miri church, Malaysia is to develop Christian education learning for adults who should understand and have skills with regard to design procedures so that Christian education programs for adults become more accommodating and effective.Abstrak: Pembelajaran pendidikan Kristen berfungsi sebagai pedoman untuk menolong pendidik Kristen dalam melatih orang-orang dewasa dalam gereja sehingga jemaat semakin memahami gambar atau konsep jati diri, peran dan tanggung jawabnya sebagai orang dewasa secara lebih jelas dan mantap dalam kehidupan sehari-hari serta dalam relasinya dengan masyarakat sekitar. Persoalan yang timbul adalah: Apakah pengertian andragogi orang dewasa? Apakah signifikan pendidikan Kristen bagi orang dewasa? Bagaimanakah strategi pembelajaran pendidikan Kristen bagi Jemaat dewasa di gereja BEM Taman Tunku Miri, Malaysia? Jawaban dari persoalan-persoalan adalah: (1) pendidikan Kristen kepada jemaat dewasa merupakan usaha mendidik atau membelajarkan warga gereja dalam segala kelompok usia yang ada, tidak terkecuali kelompok usia dewasa. (2) signifikan pendidikan Kristen bagi orang dewasa merupakan salah satu bentuk upaya gereja dalam mendidik atau membelajarkan warganya adalah dengan adanya perencanaan program pembelajaran yang didesain sedemikian rupa untuk mencapai tujuan pendidikan Kristen bagi orang dewasa. (3) Strategi pembelajaran pendidikan Kristen bagi Jemaat dewasa di gereja BEM Taman Tunku Miri, Malaysia adalah mengembangkan pembelajaran pendidikan Kristen bagi orang dewasa hendaknya memahami dan memiliki keterampilan berkenaan dengan prosedur desain sehingga demikian program pendidikan Kristen bagi orang dewasa menjadi lebih akomodatif dan efektif.